Tungsten Diselenide Nanoparticles Produced via Femtosecond Ablation for SERS and Theranostics Applications - Andrei Ushkov; Dmitriy Dyubo; Nadezhda Belozerova; Ivan Kazantsev; Dmitry Yakubovsky; Alexander Syuy; Gleb V. Tikhonowski; Daniil Tselikov; Ilya Martynov; Georgy Ermolaev; Dmitriy Grudinin; Alexander Melentev; et al. (Nanomaterials)
Due to their high refractive index, record optical anisotropy and a set of excitonic transitions in visible range at a room temperature, transition metal dichalcogenides have gained much attention. Here, we adapted a femtosecond laser ablation for the synthesis of WSe2 nanoparticles (NPs) with diameters from 5 to 150 nm, which conserve the crystalline structure of the original bulk crystal. This method was chosen due to its inherently substrate-additive-free nature and a high output level. The obtained nanoparticles absorb light stronger than the bulk crystal thanks to the local field enhancement, and they have a much higher photothermal conversion than conventional Si nanospheres. The highly mobile colloidal state of produced NPs makes them flexible for further application-dependent manipulations, which we demonstrated by creating substrates for SERS sensors.